Ductility dip cracking mechanism of Ni–Cr–Fe alloy based on grain boundary energy. (May 2013) - Chen, J Q; Lu, H; Yu, C; Chen, J M; Zhang, M L
Abstract : Inconel 690 and the companion filler metal 52M (FM-52M) have susceptibility of ductility dip cracking (DDC) in welding procedure. According to test results, DDC was not only preferential to propagate on grain boundaries vertical to loading direction but also related to grain boundary structure. To reveal the relation of grain boundary angle and cracking, a three-dimensional polycrystalline model was constructed to simulate the formation of DDC. In this work, the initiation and propagation of DDC were studied based on extended Read–Shockley formula. The results indicate that grain boundaries with approximate 45° disorientation are most prone to cracking, and the simulated DDC morphology shows agreement with experimental results. The study provides an extra method to predict DDC propagation and helps to evaluate DDC susceptibility in grain level.